A critical discourse analysis of fairclough toward “viva la vida” song by coldplay - Pudjiati, Danti; MAWARNI, VENTI; Hamdani, Haris; Wahyu Utomo, Muhammad Abdul Syukur (LPPM Universitas Mercu Buana Yogyakarta, 2023)
This study has three objectives (1) to expose the intended message of figurative expressions through the lyrics, (2) to figure out symbolic signs and gestures of Coldplay video clip “Viva La Vida” (3) to work out its implication of language learning. The data were song lyrics and symbolic cues pictured in the video clip evaluated using Fairclough’s critical discourse analysis. They were categorized by any kinds of figurative expressions delivered to disclose the intended meaning and understand symbolic appearances to find its contribution for language studying. The findings reveal that the majority of clues delivered are trying to express the story of the song about the king who is not longer to be a ruler. The use of figurative expression increases the language learners knowledge about hyperbole, personification and metaphor for they are able to explore insight and their imagination. The clues are shown expressively through the symbols of the singer and band players. Some language features used for language teaching related with parts of speech, tenses, and pronunciation. This song can be used as a teaching material to explore more comprehensive about the figurative language, symbol in literary works and to teach English as well.